Emergency blood transfusion service (report) (1939)
1939 1939 1930s 5 pages -4- Since the average hospital is expected to store about 20 to 30 pints, the 33-bottle Frigidaire unit would appear to be a very desirable refrigerator for installation at such points. Finally, it may be pointed out not only that blood storage is desirable in peace as well as in war-time, but also that these refrigerators are ideally suited to the storage of vaccine, sera, etc., and would thus be of permanent benefit to the hospital. 292/845.2/4/51